Gonisti i. e. Agonisti receptorjev TPRV1 v zdravljenju nevropatske bolečine - Rožman Klemenčič, Melita (Rehabilitacija (Ljubljana), 2019)
Introductiona: Neuropathic pain is caused by a lesion or disease of the somatosensory nervous system. Its prevalence ranges from 6.9 to 10%. It is treated with drugs and other non-pharmacological therapies. Second-line treatment include the 8 % capsaicin patch, where capsaicin binds to the TRPV1 receptor of the primary sensory neuron and results in the defunctionalization and degeneration of sensory nerve endings, thereby reducing pain. Methods: In a healthy 51-year old patient two years after caustic-allergic skin and nerve injury in the area of both ankles and calfs and surgical care with skin grafts, burning pain with intermittent electrical shock persisted, despite high doses of gabapentin. At night, the pain was exacerbated, with insomnia and consequently fatigue and poor mood. Pregabalin and duloxetine were ineffective, lidocaine patch also did not reduce the pain. We therefore applied to the skin graft an 8 % capsaicin patch. Results: After a capsaicin patch application to the skin graft, a three- to four-week delayed effect (less burning, tingling, less pain and better sleep) occurred each time. The patient reported a prolonged therapeutic effect between applications, increasing from three months after the first application to seven months after the second and 10 months after the third application. Conclusion: Treatment of persistent and severe chronic neuropathic pain with an 8 % capsaicin patch is likely to be effective and safe in skin grafts when the wound is already healed. However, more clinical data will be needed to fully evaluate the safety and efficacy of capsaicin patch use on skin grafts.
Keywords: bolečina; capsaicin; kapsaicin; kožni presadek; Neuralgia; neuropathic pain; Nevralgija; nevropatska bolečina; pain; skin graft; TRPV1